Collected stories - Hazzard, Shirley, 1931-2016 (Farrar, Straus and Giroux, 2020)
"Including twenty-eight works of short fiction in all, Shirley Hazzard's Collected Stories is a work of staggering breadth and talent. Taken together, Hazzard's short stories are masterworks in telescoping focus, "at once surgical and symphonic" (The New Yorker), ranging from quotidian struggles between beauty and pragmatism to satirical sendups of international bureaucracy, from the Italian countryside to suburban Connecticut."--Provided by publisher.